The Effect of Problem-Based Learning Models and Prior Knowledge toward Critical Thinking Skills on Human Digestive and Circulatory System - Maiyusri Eka Putri; Yuni Ahda; Azwir Anhar; Dwi Hilda Putri (Postgraduate, University of Mataram, 2023)
Technological developments demand that education is directed at learning that equips students with 21st century skills. One of them is critical thinking skills. Students' critical thinking skills can be developed through the use of appropriate learning models and supported by prior knowledge that students already have. However, the use of learning models applied in schools has not optimally developed students' critical thinking skills and tests have never been carried out to determine students' prior knowledge. One of the learning models that can develop critical thinking skills is the problem-based learning model. The purpose of this study was to determine the effect of problem-based learning models and prior knowledge on the critical thinking skills of class VIII students of SMP Negeri 1 Lengayang. This type of research is a quasi-experimental with a population of class VIII students at SMP Negeri 1 Lengayang in the odd semester of the 2022/2023 academic year. Taking two sample classes using purposive sampling technique. The design of this research is Randomized Control-Group Posttest Only Design. The instrument used in this study was a written test. The data analysis technique for testing the hypothesis is the independent sample t test and the two-way ANOVA test. The results of this study prove that: The problem-based learning model influences the critical thinking skills of class VIII students of SMP Negeri 1 Lengayang; the problem-based learning model and high prior knowledge affect the critical thinking skills of class VIII students of SMP Negeri 1 Lengayang; The problem-based learning model and low prior knowledge affect the critical thinking skills of class VIII students of SMP Negeri 1 Lengayang; The problem-based learning model has no interaction with prior knowledge in influencing the critical thinking skills of class VIII students of SMP Negeri 1 Lengayang